Digital technology and its use in the child’s educational process - zitouni, sabira (El Omda in Linguistics and Discourse Analysis, 2025)
This study aims to identify the role of the use of digital technology and methods of using it in the educational process for children, as technology is an important tool in the education process for children. It provides them with multiple opportunities to discover and learn knowledge in innovative and fun ways. Children can use computers, tablets and educational apps to improve their reading, writing, numeracy and other basic skills. Using educational games and interactive software, children can learn independently and at their own pace. Instead of traditional lessons, they can solve problems and make progress on difficult concepts through play and experimentation. This enhances their creative and collaborative thinking and problem-solving ability. Children's experience of technology in the educational process can be an enriching and fun experience. If used properly and systematically, technology can contribute to developing children's skills and increasing their interest in learning.